Design and Economic Evaluation of Solar Home System for a Residential - Kamaludin, Sulaiman Mohamed; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2024)
The growing need for sustainable energy sources worldwide, coupled with the rising price of fossil fuels, makes a deliberate move towards renewable energy sources necessary. To supplement the finite supply of conventional energy sources and address environmental issues like air pollution and climate change, solar energy is a dependable and essential option. To solve this problem, the design and financial assessment of a solar home system (SHS) for a residential flat in Parit Raja, Malaysia, are the main objectives of this research. The objectives include building a sustainable solar photovoltaic system that is both efficient and appropriate for the local environment, as well as completing comprehensive cost research. This work primarily focuses on designing a 500W SHS while considering its financial aspects, with the aim of meeting both the needs of individuals and the national energy goals effectively. The study centers on a case study in Parit Raja, Johor State, where carefully examined how power is used in single-household SHS setups. This research seeks to provide valuable insights into the practical and economic benefits of SHS for residential power generation. Therefore, the average electricity cost in Malaysia is RM0.218 per kilowatt-hour (kWh), but the COE, which represents the average cost of energy production during the system’s lifespan, is RM0.1907 per kWh. This suggests that the system is a cost-effective technique of electricity production. In this work, the design and simulation tasks were used through the assistance of HOMER software.